Alpha-1-antitrypsin globules in the liver and PiM phenotype. - Bradfield, J W (1977)
The finding is recorded of typical a1-antitrypsin globules, confirmed by immunofluorescence and immunoperoxidase methods, in the hepatocytes of a patient shown to have a normal serum antitrypsin level and normal phenotype (TiM) for a1-antitrypsin. The identification of such globules can no longer be regarded as conclusive evidence of an abnormal a1-antitrypsin phenotype.